(untitled) (Veterinary Science, 2018)
In the city of Buenos Aires, Argentine Republic, not only the census but also the records in private veterinarians allow you to estimate the animals with responsible holder, but to guarantee the success of health plans for the ethical control of urban fauna is necessary to estimate on a consistent basis. The presence of stray pets (dogs and cats) was registered in all the communes of the Autonomous City of Buenos Aires, using a systematic sampling, selecting a set of streets in each commune in the form of Greek guard. The results showed, based on 208 sightings, a total of dogs in street condition of 91,73 ± 33,12 animals every 1000 blocks